Static structural analysis of the effect of change in femoral head sizes used in Total Hip Arthroplasty using finite element method. Issue 1 (31st December 2022) - Bhawe, Aniket Kunal; Shah, Kavish Maulik; Somani, Samridhi; Shenoy B, Satish; Bhat N, Shyamasunder; Zuber, Mohammad; K N, Chethan
Abstract: The total hip prosthesis is considered one of the greatest advancements in orthopaedic surgery in the early 20 th century. In hip implant replacement, the stem is inserted into the femur and femoral head, acetabular cup, and backing cup over the stem. This felicitates the normal range of motion and stability of an individual compared to the natural hip joint. Several different types of biomaterials are used in the total hip prosthesis. Where the combination of UHMWPE, CoCrMo alloy, and Ti-6Al-4 V alloy is widely used due to their superior mechanical properties over the others. In this work, these material combinations are used for the analysis with changes in the femoral head sizes from 24 mm to 48 mm to know the best size with the better material combination. Static structural analyses are carried out using Ansys R-19. Two sets of analyses are performed for two different material combinations between Ti-6Al-4 V, CoCr, and UHMWPE. The circular cross-shaped stem with change in femoral head sizes from 24 mm to 48 mm is used for analysis. The acetabular cup and backing cup thickness are kept constant throughout the study. The size of the acetabular cup and backing cup is considered 6 mm and 4 mm respectively. Loading and boundary conditions are considered as per the ASTM standards. Hip implant with Ti-6Al-4 V for stem and a 4 mm backing cup of CoCr and 6 mm acetabular cup of UHMWPE shown the least stress value of 203.48 MPa over all the other models which are used in the analysis. This work shows the analysis to know the effect of the change in femoral head size and also the change in material combinations used in hip implants. Further experimental work can be carried out to validate the results obtained in the current work.